6.3k views
4 votes
Solve for x: 3(x + 1) = −2(x − 1) − 4

User DamiToma
by
4.8k points

2 Answers

4 votes
X=-1
I hope that helps
User Rigel Glen
by
4.9k points
3 votes

Answer:

x=

−3

2

Explanation:

Let's solve your equation step-by-step.

3(x+1)=−1(x−1)−4

Step 1: Simplify both sides of the equation.

3(x+1)=−1(x−1)−4

(3)(x)+(3)(1)=(−1)(x)+(−1)(−1)+−4(Distribute)

3x+3=−x+1+−4

3x+3=(−x)+(1+−4)(Combine Like Terms)

3x+3=−x+−3

3x+3=−x−3

Step 2: Add x to both sides.

3x+3+x=−x−3+x

4x+3=−3

Step 3: Subtract 3 from both sides.

4x+3−3=−3−3

4x=−6

Step 4: Divide both sides by 4.

4x

4

=

−6

4

x=

−3

2

User Unconditional
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.